2006
DOI: 10.1016/j.cardiores.2005.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of peroxynitrite in chemical preconditioning with 3-nitropropionic acid in rat hearts

Abstract: This is the first demonstration in the rat myocardium that 3-NP induces pharmacological preconditioning, thereby limiting infarct size, and that this effect is associated with increased NO bioavailability and reduced peroxynitrite formation due to inhibition of superoxide formation by XO and NADH oxidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
(36 reference statements)
2
15
1
Order By: Relevance
“…Researchers also confirmed 3-NP-induced lesions and oxidative damage in hippocampus (Rodríguez-Martínez et al 2004;Silva et al 2007;Karanian et al 2006;Burda et al 2005). Turan and coworkers reported that chemical preconditioning with 3-NP reduces infarct size via a mechanism that may involve increased bioavailability of NO and decreased ONOOformation (Turan et al 2006). Previous studies from different groups reported that 3-NP significantly induced oxidative damage and impaired antioxidant defense enzymes in the brain (Kumar and Kumar 2009;Kumar et al 2006Kumar et al , 2007Túnez et al 2006Túnez et al , 2007Túnez and Santamaría 2009;Pérez-De La Cruz et al 2009;Garcia et al 2008) Antioxidant drugs strategies (Curcumin, resveratrol; Kumar et al 2006Kumar et al , 2007 as well as overexpression of genes involved in attenuating oxidative stress showed a significant neuroprotective effects against 3-NP neurotoxicity (Beal et al 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Researchers also confirmed 3-NP-induced lesions and oxidative damage in hippocampus (Rodríguez-Martínez et al 2004;Silva et al 2007;Karanian et al 2006;Burda et al 2005). Turan and coworkers reported that chemical preconditioning with 3-NP reduces infarct size via a mechanism that may involve increased bioavailability of NO and decreased ONOOformation (Turan et al 2006). Previous studies from different groups reported that 3-NP significantly induced oxidative damage and impaired antioxidant defense enzymes in the brain (Kumar and Kumar 2009;Kumar et al 2006Kumar et al , 2007Túnez et al 2006Túnez et al , 2007Túnez and Santamaría 2009;Pérez-De La Cruz et al 2009;Garcia et al 2008) Antioxidant drugs strategies (Curcumin, resveratrol; Kumar et al 2006Kumar et al , 2007 as well as overexpression of genes involved in attenuating oxidative stress showed a significant neuroprotective effects against 3-NP neurotoxicity (Beal et al 1995).…”
Section: Discussionmentioning
confidence: 98%
“…In the Langendorff isolated and perfused heart model, the coronary vasodilator effect of Citrus paradisi peel extract could be NO-dependent since it was inhibited by NO synthase inhibition. This effect may be mediated by increased endothelial NO production, protection of superoxide-driven inactivation of NO released basally from endothelium (O 2 · − ), or potentiation of the NOcGMP pathway for the induction of relaxation (Villar et al, 2005;Turan et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…ROS-induced inhibition of complex II at restoration of the coronary flow has a huge effect on subsequent mitochondrial ROS production, since it provokes its inhibition. Utilization of complex II inhibitors such as 3-nitro-N-methyl-salicylamide, malonate, or 3-nitropropionic acid indeed protects the myocardium against reperfusion-induced contractile dysfunction by reducing the burst of ROS occurring ordinarily at the beginning of reperfusion (Zhang et al 2006;Turan et al 2006;Wojtovich and Brookes 2008). In our work, ischemia/reperfusioninduced inhibition of the complex II activity in young adults related to the burst of ROS occurring at early reperfusion tempered ROS release during the remaining duration of reperfusion as it was indicated by the unchanged aconitase to fumarase ratio before and after ischemia.…”
Section: Discussionmentioning
confidence: 99%